The Use of Duolingo Application in Teaching Reading Skill - Liunokas, Yanpitherszon (Institut Agama Islam Negeri Palopo, 2024)
This research deals with the teaching reading through Duolingo Application at the fourth semester students of English Education Department, Nusa Cendana University, Kupang, NTT. The population of this research is the Fourth Semester Students of English Education Department, Nusa Cendana University, Kupang, NTT. Reading test was the instrument of this research. Based on the findings and discussion, the researcher concludes that the use of Duolingo Application is effective in developing students’ reading ability at the Fourth Semester Students of English Education Department, Nusa Cendana University, Kupang, NTT. It was proven by there was a significant difference between the students’ mean score of pretest and posttest. In pretest, the students’ mean score is 26 and the students’ score in posttest is 51. In addition, the result of statistical analysis for level of significance (p=0.05). The probability value was smaller than α (0.00<0.05). it indicated that there is significant differences between the result of pre-test and post-test after giving treatment in building students’ reading skill ng by applying Duolingo Application to the fourth semester students of English Education Department, Nusa Cendana University, Kupang, NTT.